Pendampingan Siswa Madrasah Tsanawiyah dalam Memahami Sejarah dan Konsep Psikologi Perkembangan Serta Teori Perkembangan Anak-Anak - Endah Tri Wisudaningsih; Abyadisyarovito Genggong A; Aditya Firmansyah (Lembaga Pengembangan Kinerja Dosen, 2025)
This Community Service Program aims to enhance the understanding of parents, Madrasah Tsanawiyah students, and the community of Karangbong Village regarding the history of developmental psychology and major child development theories. The program was initiated due to the community’s limited knowledge of developmental concepts, which affects the quality of parenting practices. Using a descriptive qualitative approach through observation, interviews, educational sessions, and discussions, the program presented essential materials covering the history of developmental psychology, Piaget’s cognitive development theory, Erikson’s psychosocial stages, and Vygotsky’s sociocultural theory. The results indicate a significant improvement in participants’ comprehension of developmental stages and their ability to apply appropriate parenting strategies. The program also reinforced the awareness that child development is a responsibility and divine trust that must be nurtured optimally. Overall, this activity contributes to the development of informed, adaptive, and development-oriented parenting within the community.